The focusing of light through 2-D graded photonic crystals - Singh B.K.; Kumar P.; Pandey P.C. (My University, 2025)
We have investigated the strong focusing of electromagnetic waves in novel twodimensional graded photonic crystals (GPCs). The designed GPCs have the potential to use in optical systems that require compact and powerful focusing elements. © OSA 2014.